2008
DOI: 10.1016/j.poly.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of niobium and tantalum halides, MX5, with haloacetic acids and their related anhydrides: Anhydride C–H bond activation promoted by MF5

Abstract: Niobium and Tantalum pentahalides, MX 5 (1), react with acetic acid and halo-substituted acetic acids, in 1:1 ratio, to give the dinuclear complexes [MX 4 (µ-OOCMe)] 2 [M = Nb, X = Cl, 2a; M = Ta, X = Cl, 2b, Br, 2c] and [MCl 4 (µ-OOCR)] 2 [M = Nb, R = CH 2 Cl, 4a, CHCl 2 , 4c, CCl 3 , 4e, CF 3 , 4g, CHBr 2 , 4i, CH 2 I, 4j; M = Ta, R = CH 2 Cl, 4b, CHCl 2 , 4d, CCl 3 , 4f, CF 3 , 4h]. The solid state structures of 2b and 4e have been ascertained by X ray diffraction studies. The reactions of 1 with acetic anh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…A similar complex was reportedly formed by mixing NbCl 5 and acetic acid to form niobium chloro carboxylate, with one carboxylate ion coordinating to two Nb 5+ ions in a bridging configuration. 29 Upon converting the NbP-40 to NbP-120, we hypothesize that the quenching of LMCT absorption is due to the conversion from a complex-like composition to an oxide-like composition, consistent with NbP-120 having absorption residing largely in the UV region. NbP-120, behaving similarly to an oxide, is referred to as a niobium oxo cluster for the remaining discussion.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…A similar complex was reportedly formed by mixing NbCl 5 and acetic acid to form niobium chloro carboxylate, with one carboxylate ion coordinating to two Nb 5+ ions in a bridging configuration. 29 Upon converting the NbP-40 to NbP-120, we hypothesize that the quenching of LMCT absorption is due to the conversion from a complex-like composition to an oxide-like composition, consistent with NbP-120 having absorption residing largely in the UV region. NbP-120, behaving similarly to an oxide, is referred to as a niobium oxo cluster for the remaining discussion.…”
Section: Resultsmentioning
confidence: 55%
“…It was reported that niobium chloro carboxylate will react with acid anhydride to form acyl chloride. 38 In our reaction environment, the analogues would be oleic anhydride and oleoyl chloride. In the IR and 1 H-NMR spectra of NbP-40 ( Figure 2d and 2e), the C=O stretch (1802 cm -1 ) and triplet resonance at 2.88 ppm can be assigned to oleoyl chloride.…”
Section: Precursor Characterization and Synthetic Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…36 These reactions preserve altogether the highly energetic M-F bonds, thus preventing the activation of O-H bonds. On the other hand, it has been known since many years that the heavier pentahalides MX 5 (M = Nb, Ta; X = Cl, Br, I) react with alcohols/phenols 1,34,75 or carboxylic acids, 76,77 in variable molar ratios, giving alcoholato/carboxylato derivatives via O-H bond cleavage and HX release. The latter derivatives generally maintain the dinuclear structure typical of the starting materials, unless additional donor atom is present in the organic moiety.…”
Section: Stabilization Of Uncommon Cationsmentioning
confidence: 99%